1992
DOI: 10.1107/s0108768191013101
|View full text |Cite
|
Sign up to set email alerts
|

La1.16Mo8O16: a hollandite-related compound with an incommensurate modulated structure

Abstract: The hollandite‐related structure La1.16Mo8O16, Mr = 1184.66, tetragonal, , a = 9.983 (1), c = 2.8890 (5) Å, V = 287.9 Å3, Z = 1, Dx = 6.83 g cm−3, (Mo Kα) = 0.71069 Å, μ = 126 cm−1, F(0000) = 530, room temperature, R = 0.041 for 1145 unique reflections with I3σ(I). At room temperature the compound exhibits a one‐dimensional incommensurate modulated structure with a modulation wavevector q* = 0.608 (1)c*. Both a displacive modulation wave, acting on La, Mo and O atoms, and a modulation wave governing the occupa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…The superspace group was easily identified as I4/m(00g)00, since there were no systematic extinctions, other than those related to the I cell centering. The possibility of a non centrosymmetric space group (I4(00g)00), as found in the literature [20] in another hol- Fig. 2.…”
Section: X-ray Diffraction Data Processingmentioning
confidence: 95%
“…The superspace group was easily identified as I4/m(00g)00, since there were no systematic extinctions, other than those related to the I cell centering. The possibility of a non centrosymmetric space group (I4(00g)00), as found in the literature [20] in another hol- Fig. 2.…”
Section: X-ray Diffraction Data Processingmentioning
confidence: 95%
“…In hollandite-type compounds commensurate and incommensurate superstructure reflections and diffuse scattering are commonly observed (12)(13)(14)(15)(16)(17)22). Several models of atoms distributions within the tunnels have been proposed.…”
Section: Distribution Of the Barium Atomsmentioning
confidence: 98%
“…It has been indeed observed that besides the ideal tetragonal hollandite structure, there exist orthorhombic and monoclinic distortions (2,(8)(9)(10)(11). But most importantly, modulation and disorder phenomena concerning the particular arrangement of the cations in the large four-sided tunnels are commonly observed (12)(13)(14)(15)(16)(17). Moreover, a synthetic hollandite-type has been observed by dehydration of the psilomelane (Ba, H O)Mn O (18) at 550°C.…”
Section: Introductionmentioning
confidence: 96%
“…For a conventional incommensurately modulated structure, this would certainly represent a rather simpler indexation scheme. Leligny et al, 1992). It is confirmed by EDPs such as the [ 1 102] f zone axis EDP shown in Fig.…”
Section: Electron Diffractionmentioning
confidence: 60%